Collaboration After Disaster: Explaining Intergovernmental Collaboration During the EPA Gold King Mine and TVA Coal Ash Recoveries. Issue 1 (28th August 2018) - Fisk, Jonathan M.; Good, A. J.; Nelson, Steven
Abstract : When disaster strikes, the post‐disaster politics often increase in complexity, importance, and ferocity. Disasters and attendant recovery efforts quickly occupy space on public agendas, involve a myriad of actors, and often require coordination from multiple stakeholders. This research examines two such instances and focuses on the recovery efforts following spills at the Tennessee Valley Authority's Kingston, TN coal‐fired power plant and the Environmental Protection Agency's Gold King Mine site. Using primary and secondary sources, this project identifies that unresolved historical issues, problem complexity, and action type are likely to make intergovernmental collaboration during recovery more difficult.